IN VITRO CYTOTOXICITY AND GLUCOSE UPTAKE ACTIVITY OF SIDDHA FORMULATION NAAVAL KOTTAI MATHIRAI IN L-6 CELL LINES - S, *Sivakkumar; L, Juliet; G, Ganapathy; V, Banumathi. (International Journal of Ayurveda and Pharma Research, 2016)
The Siddha system of medicine is a traditional Indian system which evolved with the development of mankind and is more of an evolution rather than invention. Siddha system describes the health of an individual as an ideal perfect state of the physical, physiological, social, and spiritual components of a human being. Diabetes is a chronic disorder linked with the metabolism of carbohydrate, protein and fat due to absolute or relative deficiency of insulin secretion with or without varying degree of insulin resistance. There is sufficient number of drugs in different systems of medicine for the management of diabetes but the incidence of type-II diabetes is too high. In Siddha system many more traditional formulations are available. Most of these medicines are clinically used by Siddha physicians but have not been evaluated scientifically. Naaval kottai Mathira is a anti-diabetic Siddha herbal formulation which is prepared from the seeds of Syzygium cumini and leaves of Aristolochia bracteolata and it has been used for the management of Diabetes mellitus (Madhumegam). The aim of the present study is to evaluate the cytotoxicity and glucose uptake activity of herbal preparation NKM using L-6 cell lines. The results showed that the test drug did not confer any cytotoxicity and the drug NKM showed better glucose uptake potential. The result of glucose uptake percentage for standard drug Rosiglitazone is 113.26±7.72 and 32.67±4.25 for Naaval Kottai Mathirai. The findings of this investigation concluded that the study drug NKM has anti-diabetic activity in glucose uptake assay.